Hubungan Tingkat Stres, Aktivitas Fisik dan Kualitas Tidur dengan Dismenore pada Mahasiswi Gizi Program Sarjana Fakultas Kesehatan Universitas Pembangunan Nasional Veteran Jakarta - Nadiyah Hasanah (2022)
Dysmenorrhea is felt generally appears at the same time as the start of menstruation which lasts a few days until it reaches the peak of menstruation. Most young women in Indonesia experience dysmenorrhea during menstruation, but only a few of them find out about the incidence of dysmenorrhea. The aim of the study was to determine the relationship between stress levels, physical activity and sleep quality on dysmenorrhea in students of the nutrition study program of University Of Pembangunan Nasional Veteran. Jakarta. This study was structured using an observational research design with a cross sectional research design involving 81 respondents with the Total Sampling technique. The analysis used is the Chi-Square test. The results of the bivariate analysis test showed that there was a relationship between stress levels (p=0.00), physical activity (p=0.000) and sleep quality (p=0.000) with the incidence of dysmenorrhea. Respondents can maintain a healthier lifestyle both psyichologically and physically so that respondent's dysmenorrhea does not interfere with daily activities and productivity